Determinan Perilaku Hidup Sehat Pada Remaja Di Sekolah Menengah - Harlina Harlina (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Healthy lifestyle behaviors in adolescents are important factors in maintaining health and preventing various health problems in adulthood. Adolescence is a transitional period that is vulnerable to the formation of risky behaviors, so it is necessary to understand the factors that influence healthy lifestyle behaviors. This study aims to determine the determinants of healthy lifestyle behaviors in adolescents in secondary schools. This study used a quantitative method with an analytical design and a cross-sectional approach. The research sample consisted of secondary school students at School X. Data were collected using questionnaires and analyzed using statistical tests. The results showed that knowledge, attitudes, family support, and school environment were significantly associated with healthy lifestyle behaviors among adolescents (p < 0.05). The conclusion of this study is that healthy lifestyle behaviors among adolescents are influenced by various individual and environmental factors, thus requiring comprehensive health promotion efforts in the school environment.